Multiple autophosphorylation sites are dispensable for murine ATM activation in vivo - J. Daniel; Manuela Pellegrini; Ji‐Hoon Lee; Tanya T. Paull; Lionel Feigenbaum; André Nussenzweig (2008)
Cellular responses to both physiological and pathological DNA double-strand breaks are initiated through activation of the evolutionarily conserved ataxia telangiectasia mutated (ATM) kinase. Upon DNA damage, an activation mechanism involving autophosphorylation has been reported to allow ATM to phosphorylate downstream targets important for cell cycle checkpoints and DNA repair. In humans, serine residues 367, 1893, and 1981 have been shown to be autophosphorylation sites that are individually required for ATM activation. To test the physiological importance of these sites, we generated a transgenic mouse model in which all three conserved ATM serine autophosphorylation sites (S367/1899/1987) have been replaced with alanine. In this study, we show that ATM-dependent responses at both cellular and organismal levels are functional in mice that express a triple serine mutant form of ATM as their sole ATM species. These results lend further support to the notion that ATM autophosphorylation correlates with the DNA damage–induced activation of the kinase but is not required for ATM function in vivo.